Zinc nutrition optimization for better cotton productivity on alkaline calcareous soil - M. Ashraf; F. Qamar; M. Mehran; S. Masood; S. M. Shahzad; M. S. Javed; M. T. Azhar (Journal of Cotton Research)
Abstract Background Zinc (Zn), being the most deficient micronutrient, can largely limit plant growth and development on alkaline calcareous soil. Crop species and varieties within species differently require Zn for optimum productivity. The current study aimed to optimize Zn level and mode of application for better growth, yield, and fiber quality of cotton (Gossypium hirsutum L.). The experimental plan comprised a control group with no Zn application, three Zn levels through soil application, i.e. 5 mg·kg− 1 (SZn5), 10 mg·kg− 1 (SZn10), and 15 mg·kg− 1 (SZn15), two levels of foliar application including 0.5% (FZn0.5) and 1% (FZn1) Zn solution, and various combinations of soil plus foliar application. Two cotton cultivars, CIM-663 (Bt) and Cyto-124 (non-Bt) were used, and each treatment was replicated thrice. Results Zinc nutrition caused a significant (P ≤ 0.05) improvement in growth, yield, physiological, and fiber quality characteristics of both cotton cultivars. All levels and modes of Zn application were found effective in improving cotton productivity on alkaline calcareous soil. However, integrated soil application and foliar spray showed superiority over sole soil or foliar application. Among different treatments, SZn15 + FZn1 caused the highest improvement in most of the observed growth and yield traits. The said treatment maximally increased the leaf Zn concentration by 270.5% and 218.4% with a subsequent increase in plant height 23.2% and 28.0%, monopodial branches 40.7% and 42.1%, sympodial branches 37.2% and 35.2%, seed cotton yield 32.5% and 36.6%, and lint yield 30.0% and 34.6% in CIM-663 and Cyto-124, respectively, compared with the control. SZn15 + FZn1 also caused the highest increase in relative water contents 32.6% and 22.4%, chlorophyll contents 92.0% and 67.1%, and stomatal conductance 112.8% and 100.8% in CIM-663 and Cyto-124, respectively, compared with the control. Among the fiber quality characteristics, fiber fineness was maximally improved by 19.7% and 15.9% in CIM-663 and Cyto-124, respectively, with SZn15 + FZn1 compared with the control. Leaf Zn concentration was positively correlated with fiber length (R 2 = 0.717 3), fiber strength (R 2 = 0.548 3), and fiber fineness (R 2 = 0.637 9) of both cotton cultivars grown with different levels and application modes of Zn. The benefit-cost ratio was remarkably improved with Zn nutrition, and the highest value of 1.64 was found in CIM-663 at SZn10 + FZn1 and SZn15 + FZn1. Conclusion The plant growth, physiological, yield, and fiber quality characteristics of cotton cultivars were significantly improved with Zn supply at different levels and modes of application. SZn15 + FZN1 could be recommended to get optimum seed cotton yield and fiber quality of cotton on alkaline calcareous soil.